Smart Data and Computational Intelligence Proceedings of the International Conference on Advanced Information Technology, Services and Systems (AIT2S-18) Held on October 17 - 18, 2018 in Mohammedia - Khoukhi, Faddoul; Bahaj, Mohamed; Ezziyyani, Mostafa (Lecture Notes in Networks and Systems,, 2019)
This book gathers the proceedings of the International Conference on Advanced Information Technology, Services and Systems (AIT2S-18), which was held in Mohammedia, Morocco on October 17-18, 2018. Presenting the latest research in the fields of Modern Information Engineering Concepts and Communication Systems, the book will also be of interest to those working in emerging fields such as Advances in Networking and Sensor Networks, Advances in Software Engineering, Multimedia Systems, E-learning, Big Data, Intelligent Information Systems and Advances in Natural Language Processing.